2021
DOI: 10.5115/acb.21.105
|View full text |Cite
|
Sign up to set email alerts
|

The role of hesperidin in ameliorating retinal changes in rats with experimentally induced type 1 diabetes mellitus and the active role of vascular endothelial growth factor and glial fibrillary acidic protein

Abstract: Patients with type 1 diabetes mellitus (T 1 DM) are vulnerable to developing diabetic retinopathy even under insulin therapy. Thus, this study was designed to evaluate the efficacy of hesperidin and insulin in rats with T 1 DM compared with insulin alone in improving diabetic retinal changes. Eighty rats were divided into four equal groups: group I, control rats without diabetes; group II, untreated rats with diabetes; group III, rats with diabetes treated daily wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For H&E and toluidine blue staining, eyeballs specimens were embedded in paraffin after fixation in 10% formalin solution in normal saline. Blocks were sectioned sagittal at eye bulb equator (100–150 μm away from the optic nerve) according to Shehata et al [ 22 ], 4–5 microns thickness then they were hoarded on glass slides, deparaffinized for histopathological examination [ 23 ]. The slides examined by the light electric microscope (LEICA ICC50 W), Department of Human Anatomy & Embryology, Faculty of Medicine, Zagazig University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For H&E and toluidine blue staining, eyeballs specimens were embedded in paraffin after fixation in 10% formalin solution in normal saline. Blocks were sectioned sagittal at eye bulb equator (100–150 μm away from the optic nerve) according to Shehata et al [ 22 ], 4–5 microns thickness then they were hoarded on glass slides, deparaffinized for histopathological examination [ 23 ]. The slides examined by the light electric microscope (LEICA ICC50 W), Department of Human Anatomy & Embryology, Faculty of Medicine, Zagazig University.…”
Section: Methodsmentioning
confidence: 99%
“…Although retinal toxicity in VGB-treated patients may be Original Article https://doi.org/10.5115/acb. 22.006 eISSN 2093-3673 asymptomatic, peripheral VFD is severe in the form of irreversible peripheral vision loss in 30%-50% of adult patients [12,13], variable degrees of retinal atrophy, and decrease of visual function in 15% of children and 15%-31% of infants [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has shown a potent antioxidant activity which helps to safeguard against various chronic diseases such as Diabetes mellitus [ 2 , 8 ]. Hsd depicts auspicious antidiabetic action as it improves insulin sensitivity, and therefore prevents hyperglycemia in both Type 1 and Type 2 diabetes [ 9 11 ]. It was also reported that Hsd had protective effects against diabetic nephropathy and neuropathy [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%